O Estágio Profissional: Um passo fundamental na formação de um futuro Professor de Educação Física - Nuno Daniel Mendes Machado (2022)
This document was prepared within the scope of the Professional School Placement curricular unit, inserted in the second year of the 2nd cycle of studies, leading to obtaining a Master's degree in Physical Education Teaching in Basic and Secondary Education at the Faculty of Sports of the University of Porto (FADEUP). The same goes through a report of experiences during the School Placement through a reflective process using the existing literature. The School Placement took place at a school, in the district of Braga, which belongs to a school grouping in the same district. This report is divided into five main parts: one where a personal and institutional framework is made, another where I talk about the organization and management of teaching and learning, one about a scientific study carried out during the School Placement, another part that addresses my participation in the school and in the activities carried out by it and, finally, one where I present my conclusions and future perspectives. In the scientific study, four classes are analyzed, two from the 7th grade and the other two from the 9th grade. This study aims to understand the influence of the Covid-19 pandemic on the teaching and learning process of students and what adaptations this led teachers to need to make. This document is thus my first impact with the responsibility and work of being a teacher, the first time that I have played such an important role with so many social interactions. This is the journey of training a future Physical Education Teacher.